2021
DOI: 10.1136/bmjsem-2020-000957
|View full text |Cite
|
Sign up to set email alerts
|

Objectively quantified physical activity and sedentary behaviour in a young UAE population

Abstract: ObjectivesThere is a lack of public awareness of the importance of engaging in physical activity (PA) in the United Arab Emirates (UAE). Nearly 58% of the UAE adult population self-reports as being physically inactive although little accelerometer data currently exists. The aim of this study was to obtain the first dataset that objectively quantifies PA and sedentary behaviour (SB) in young UAE adults.MethodsThis cross-sectional study recruited 140 university students. Body composition and accelerometry was as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 24 publications
(25 reference statements)
2
13
0
Order By: Relevance
“…In addition, compared with the WHO guidelines, our findings showed that young adults did not meet the guidelines of at least 150–300 min of MPA or 75–150 min of VPA or 150 min of MVPA per week. These findings were in line with previous studies worldwide [ 41 , 42 , 43 , 44 , 45 ] that showed that young adults did not follow the recommended amount of PA per week. Similar findings were observed for older adults, indicating that older adults also did not follow international guidelines for PA.…”
Section: Discussionsupporting
confidence: 93%
“…In addition, compared with the WHO guidelines, our findings showed that young adults did not meet the guidelines of at least 150–300 min of MPA or 75–150 min of VPA or 150 min of MVPA per week. These findings were in line with previous studies worldwide [ 41 , 42 , 43 , 44 , 45 ] that showed that young adults did not follow the recommended amount of PA per week. Similar findings were observed for older adults, indicating that older adults also did not follow international guidelines for PA.…”
Section: Discussionsupporting
confidence: 93%
“…showering) that could get the activity monitor wet. Normal daily physical activity for young adults is 6300-7840 steps and 37-51 min of time spent > 3METs [17].…”
Section: Actigraphymentioning
confidence: 99%
“…Recently, a multisociety Delphi consensus on new fatty liver disease nomenclature replaced NAFLD with the new term metabolic dysfunction-associated steatotic liver disease (MASLD) [1]. Evidence shows that MASLD is strongly associated with obesity, insulin resistance and other components of the metabolic syndrome, such as hypertension, type II diabetes and dyslipidemia [2][3][4][5][6]. It can present at various stages, beginning with a simple fatty liver showing no symptoms of nonalcoholic steatohepatitis, also replaced by the new term metabolic dysfunction-associated steatohepatitis [1], progressing to cirrhosis, and hepatocellular carcinoma if untreated, constituting a significant public health concern [7].…”
Section: Introductionmentioning
confidence: 99%